Useful technologies for doubling farmers income - S., Vithlani Nipa (Indian Farming, 2018)
Doubling real income of farmers by 2022 is a formidable task but it can be possible only through the proper implementation of the appropriate strategies. Public R & D institutions should be supported to develop capacity in areas of technologies such as biotechnology which appear to have great potential. Farming is a skilled-profession and hence people could be skilled and motivated through various skill-development programmes of the government. Lucrative avenues can be created for those who want to leave agriculture and incentives and skills those who want to enter/ continue this occupation. Higher price realization by farmers need to be achieved through various price realization market reforms like e-NAM and various provisions of APMC Act. Promotion of initiatives like Soil-health Card, ICT-based agricultural extension, formation of FPO’s, Integrated Farming System. Concerted and well – coordinated efforts are required to be made between the centre and the states.